1996
DOI: 10.1159/000289029
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Cognitive Factors Associated with Adherence to Dietary and Fluid Restriction Regimens by People on Chronic Haemodialysis

Abstract: Background: Failure by people on chronic haemodialysis to adhere adequately to dietary and fluid restrictions can have serious medical consequences. Numerous psychosocial factors possibly associated with adherence have been investigated in previous research. However, most previous studies have examined one or a few variables in isolation, and have tended to focus on sociodemographic variables not easily amenable to intervention. Much previous work has tended to ignore potential differences in adherence between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 23 publications
3
52
0
1
Order By: Relevance
“…Depressive affect can directly influence poor adherence to diet and fluid regimens (16). Furthermore, chemical brain alterations in depressed patients may affect cognitive dysfunction (which may manifest as poor adherence) (17), and cognitive dysfunction has been associated with depressive affect in HD patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…Depressive affect can directly influence poor adherence to diet and fluid regimens (16). Furthermore, chemical brain alterations in depressed patients may affect cognitive dysfunction (which may manifest as poor adherence) (17), and cognitive dysfunction has been associated with depressive affect in HD patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…The commonest sources of data for adherence to medications and dietary restrictions are sequential values of biochemical indices [5] which have direct implications for health outcome. The frequently used measures are interdialytic weight gain (IWG), as an index of compliance for fluid intake, predialysis serum potassium (K) and blood urea nitrogen (BUN) as measures of dietary compliance and serum phosphate (PO 4 ) as a parameter for medication intake [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the findings have suggested that non-compliance among haemodialysis patients is a complex affair which can arise from family stress, anxiety and discord [11, 12, 13]. Further variables include: malnutrition as a result of an unimaginative or incomprehensible dietary regime [12], the absence of a supervised, ongoing exercise programme [15], health beliefs and personality [6], the onset of emotional fatigue or depression [17, 18, 19], social worker input [13], participatory control of patients [20], patient reward systems [21]and counselling [22, 23, 24, 25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…These include a single or combination of measures at either one point in time or over a specified period [5, 6, 7, 8, 9, 10, 11, 12, 13, 14]. …”
Section: Diagnosis Of Non-compliance In Patients Receiving Haemodialysismentioning
confidence: 99%
See 1 more Smart Citation